Melhoria da qualidade de jerked beef pela substituição de nitrito de sódio por extratos naturais de própolis e erva mate como agente antioxidante - Gaino, Vanessa Oliveira (2015)
Jerked beef, an industrial meat product obtained from beef with the addition of sodium chloride and curing salts and subjected to a maturing and drying process is a typical Brazilian product which has been gradually discovered by the consumer. The replacement of synthetic antioxidants by natural substances with antioxidant potential due to possible side effects discovered by lab tests, consumer health, is being implemented by the meat industry. This study aimed to evaluate the lipid oxidation of jerked beef throughout the storage period by replacing the sodium nitrite by natural extracts of propolis and Yerba Mate. For jerked beef processing brisket was used as raw material processed in 6 different formulations: formulation 1 (control - in nature), formulation 2 (sodium nitrite - NO), formulation 3 (Yerba Mate - EM), formulation 4 (propolis extract - PRO), formulation 5 (sodium nitrite + Yerba Mate - MS + NO), formulation 6 (propolis extract + sodium nitrite - PRO + NO). The raw material was subjected to wet salting, dry salting (tombos), drying at 25°C, packaging and storage in BOD 25°C. Samples of each formulation were taken every 7 days for analysis of lipid oxidation by the TBARS method. In all formulations, were carried out analysis of chemical composition at time zero and sixty days of storage. The water activity analysis and color (L *, a *, b *) was monitored at time zero, thirty and sixty days of storage. The Salmonella spp count, Coliform bacteria, Termotolerant coliforms and coagulase positive staphylococci were taken at time zero and sixty days. The activity of natural antioxidants evaluated shows the decline of lipid oxidation up to 2.5 times compared with the product in natura and presented values with no significant differences between treatments NO and EM, confirming the potential in minimize lipid oxidation of Jerked beef throughout the 60 days of storage. The results also showed that yerba mate has a higher antioxidant capacity compared to the propolis except the PRO + NO formulation. When associated with yerba mate with sodium nitrate, TBARS values become close to values obtained only for the control samples with the addition of sodium nitrite. The proximal composition of the formulations remained within the standards required in the IN nº22/2000 for jerked beef. Samples that differ significantly at 5% are directly related to the established type of formulation. The count of microorganisms was within the standards of the DRC nº12/2001 required for matured meat products. The intensity of the red (a*) decreased with storage time and increase the intensity of yellow (b*) indicates a darkening of the product despite L* also have been increased. These results suggest that yerba mate is a good alternative to meat industry in reducing healing addition salts when associated with another antioxidant.